2022
DOI: 10.1007/s12144-022-03010-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the latent structure of the Ruminative Thoughts Style Questionnaire across countries, gender, and over time

Abstract: The present work aimed to extend the evidence of the structure validity of the Ruminative Thought Style Questionnaire (RTSQ) 15-item version testing: (1) the structure of two competing models (i.e., four-factor correlated model vs a second-order factor model); (2) the measurement invariance of the final model across four countries (U.S., Spain, Argentina, and the Netherlands) and gender groups (male and female); and (3) the invariance across three assessment waves in a subsample of Spanish youths. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rumination was assessed using the 15-item version of the Ruminative Thought Style Questionnaire (RTSQ; Tanner et al, 2013 ; Spanish version, Bravo et al, 2018a ), in which participants respond to what extent the items described them on the basis of a 7-point scale (1, Not at all; 7, Very Well ). The RTSQ has shown evidence of reliability and validity among undergraduate students and over time, both in English and Spanish speakers ( Bravo et al, 2018a ; Vidal-Arenas et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Rumination was assessed using the 15-item version of the Ruminative Thought Style Questionnaire (RTSQ; Tanner et al, 2013 ; Spanish version, Bravo et al, 2018a ), in which participants respond to what extent the items described them on the basis of a 7-point scale (1, Not at all; 7, Very Well ). The RTSQ has shown evidence of reliability and validity among undergraduate students and over time, both in English and Spanish speakers ( Bravo et al, 2018a ; Vidal-Arenas et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Open Data: We confirm that there is sufficient information for independent research to reproduce all of the reported results (Vidal-Arenas et al, 2023). The information needed to reproduce all of the reported results are openly accessible at https://osf.io/jz4ge/?view_only=ea57ac ad6e6a4a6e86fa5a57caf493c9 Open Materials: We confirm that there is sufficient information for independent research to reproduce all of the reported methodology (Vidal-Arenas et al, 2023). Preregistration of Studies and Analysis Plans: This study was not preregistered.…”
Section: Conflict Of Interestmentioning
confidence: 75%